1997
DOI: 10.1002/(sici)1097-0215(19970611)71:6<924::aid-ijc2>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

A case‐control study of diet and lung cancer in Northeast China

Abstract: A case-control study involving interviews with 227 lung-cancer cases and 227 matched hospital controls was conducted in Heilongjiang Province in northeast China to examine the influence of dietary factors on the risk of developing lung cancer. Lung-cancer cases were all incident cases judged to be suitable candidates for tumor removal by surgery. Controls were selected among hospitalized patients with non-neoplastic and non-lung disease. The overall male lung-cancer risks associated with cigarette smoking were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
29
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 27 publications
5
29
0
Order By: Relevance
“…There is inconsistent evidence that Se intake may reduce lung cancer risk (14,19,20). Our null finding is probably not due to an inadequate range of Se intake, because Se intake in our control population is comparable with national estimates (21).…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…There is inconsistent evidence that Se intake may reduce lung cancer risk (14,19,20). Our null finding is probably not due to an inadequate range of Se intake, because Se intake in our control population is comparable with national estimates (21).…”
Section: Discussionsupporting
confidence: 41%
“…Cu, Zn, Se, Fe, and Ca are involved in reactive oxygen species metabolism (1-3, 6, 11) and are cofactors for enzymes needed for DNA stability and signal transduction pathways (1-3). Because these functions of Cu, Zn, Se, Fe, and Ca are implicated in the initiation and progression of lung cancer, we postulated that the joint In three studies of dietary Zn intake and lung cancer risk, two reported an inverse association (12,13) and one reported a positive association (14). Two studies of plasma/serum Zn and lung cancer revealed inconsistent results (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…In southwest China, a study among male residents of a mining community reported a 60% reduction in risk at the highest level of bean curd intake and a statistically significant inverse trend (p Ͻ 0.01). 25 Two other studies among Chinese men and women found a non-significant reduction of 40% 26 and no association 27 with higher intake of soy products. A study in Hong Kong among Chinese non-smoking women found an elevated, but not statistically significant, risk among low (OR ϭ 1.5) and medium (OR ϭ 1.6) consumers of tofu and soy products relative to high consumers.…”
Section: Discussionmentioning
confidence: 88%
“…Several [5, 10-12, 15, 19, 21, 31-34], but not all [8,[35][36][37] case-control studies reported significant positive associations between total meat intake and lung cancer risk, while most cohort studies reported nonsignificant increased risks usually of about 20-30% [14,[38][39][40][41][42]. All but two case-control studies [43,44] of red meat intake and lung cancer reported elevated risks [12,13,15,[19][20][21]45] and three cohort studies also reported elevated risk [14,22,46].…”
Section: Discussionmentioning
confidence: 99%